Karl Polanyi on economy and society: a critical analysis of core concepts. Issue 1 (2nd January 2017) - Hodgson, Geoffrey M.
Abstract: The Review of Social Economy was founded to highlight the irreducible social aspects of economic activity. Yet, the nature of the 'social' and the 'economic' are both unresolved, and they are much more problematic than often assumed. This article probes Karl Polanyi's depiction of the relationship between the 'social' and the 'economic' and subsequent discourse on 'embeddedness'. In his Great Transformation (1944) Polanyi associated the 'economic' with motives of material gain, while 'social' referred to norms of reciprocity and redistribution: his distinction between the 'social' and the 'economic' then focused primarily on different kinds of motivation. But in a 1957 essay he brought in different kinds of institutions that engender different types of motivation. Polanyi (1944) argued that after 1800 Britain was transformed into a market-oriented 'economic' system, based on motives of greed and material gain. He also proposed that an effective market system had to be 'self-adjusting' and free of political interference, despite his important additional claim that the state was involved in its creation. Some of Polanyi's core concepts and arguments are contradictory and problematic, and need to be reconsidered, especially if his enduring insights are to be salvaged.